The relationship between influenza vaccine hesitancy and vaccine literacy among youth and adults in China - Wang, Li; Guo, Mengjie; Wang, Yan; Chen, Ren; Wei, Xiaolin (Frontiers in Immunology, 2024)
Objectives: The present study aimed to assess influenza vaccine hesitancy and vaccine literacy levels among youth and adults in China, as well as the association between them. Methods: An online cross-sectional survey was conducted in Mainland China. Participants' total vaccine literacy and three sub-dimension vaccine literacy (knowledge literacy, competence literacy, and decision-making literacy) were assessed by a validated vaccine literacy scale.Having received influenza vaccination in the past three years or intending to accept it in next influenza season indicates less influenza vaccine hesitancy.Results: Among 997 participants, a sub-optimal vaccine literacy was observed, with a mean score of 66.83±10.27. Regression models 1-4 revealed that participants with middle (aOR: 1.431, P=0.039, 95% CI: 1.018~2.010) or high (aOR: 1.651, P=0.006, 95% CI: 1.157~2.354) total vaccine literacy, as well as those with high competence literacy (aOR: 1.533, P=0.017, 95% CI:1.079~2.180) , or high decision-making literacy (aOR: 1.822, P=0.001, 95% CI:1.261~2.632) were more likely to have been vaccinated against influenza at least once in past three years. However, those with a high knowledge literacy were associated with a lower influenza vaccine rate (aOR: 0.676, P=0.046, 95% CI: 0.460~0.994). Regression models 5-8 revealed that participants with middle (aOR: 1.661, P=0.008, 95% CI: 1.142~2.414) or high total vaccine literacy (aOR: 2.645, P=0.000, 95% CI: 1.774~3.942) , as well as those with middle (aOR: 1.703, P=0.005, 95% CI: 1.177~2.464) or high competence literacy (aOR: 2.346, P=0.000, 95% CI: 1.159~3.461), or high decision-making literacy (aOR: 2.294, P=0.000, 95% CI: 1.531~3.436) were more likely to express the willingness to receive the influenza vaccine in the next influenza season.The participants' influenza vaccine hesitancy was negatively associated with their total vaccine literacy levels and two of the three